2014
DOI: 10.1007/s13224-014-0559-7
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Study of Contraceptive Vaginal Ring (NuvaRing®) in Normal Daily Practice in Indian Women

Abstract: The study demonstrated that NuvaRing(®) is a highly effective contraceptive method with an excellent cycle control. It is well tolerated and accepted by Indian women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 10 publications
(18 reference statements)
2
23
0
Order By: Relevance
“…Our results indicate that some women express initial concerns about ring use, but that these concerns can be overcome once individuals commit to using the method and avail themselves of necessary and accurate information. The findings support previous work suggesting that once most users complete an adjustment phase, they are quite satisfied with the method and are highly willing to recommend it to others . This is also consistent with data published in 2016 from an early clinical trial of ring use for HIV prevention, which found that ring‐related concerns declined or resolved with use .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results indicate that some women express initial concerns about ring use, but that these concerns can be overcome once individuals commit to using the method and avail themselves of necessary and accurate information. The findings support previous work suggesting that once most users complete an adjustment phase, they are quite satisfied with the method and are highly willing to recommend it to others . This is also consistent with data published in 2016 from an early clinical trial of ring use for HIV prevention, which found that ring‐related concerns declined or resolved with use .…”
Section: Discussionsupporting
confidence: 89%
“…The fi ndings support previous work suggesting that once most users complete an adjustment phase, they are quite satisfi ed with the method and are highly willing to recommend it to others. 22,23 This is also consistent with data published in 2016 from an early clinical trial of ring use for HIV prevention, which found that ring-related concerns declined or resolved with use. 60 Anticipating and addressing women' s initial concerns and the inconveniences they may experience are potential intervention strategies for promoting use of and preventing early discontinuation of the ring.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Studies in Europe, North America and India have shown that there are no differences in the types and frequencies of systemic side effects in NuvaRing® users compared to oral contraceptive users [ 2 4 , 17 21 ]. Some of the systemic side effects that were commonly reported in those studies, and are often attributed to oestrogens, were either not reported at all by our Rwandan participants (emotional liability, breast tenderness, and acne) or were infrequently reported (nausea).…”
Section: Discussionmentioning
confidence: 99%
“…60 It is effective (Pearl index, 1-3), 62 controls the menstrual cycles, 63 and has the advantage of a lower concentration of ethinyl estradiol compared with combined hormonal contraceptives, thus minimizing the adverse events related to ethinyl estradiol. 62,64,65 In a randomized trial, the vaginal ring group showed that exposure to ethinyl estradiol was significantly 3.4 times lower than in the patch group and 2.1 times lower than in the combined hormonal contraception group. Serum ethinyl estradiol levels of patients showed much lower variations with the vaginal ring than with the patch or combined hormonal contraceptives.…”
Section: The Vaginal Ringmentioning
confidence: 99%